Does Financial Structure Matter for Poverty? Evidence from Developing Countries - Kpodar, Kangni; Singh, Raju Jan (2012)
Although there has been research looking at the relationship between the structure of the financial system and economic growth, much less work has dealt with the importance of bank-based versus market-based financial systems for poverty and income distribution. Empirical evidence has indicated that the structure of the financial system has little relevance for economic growth, suggesting that the same could be true for poverty since growth is an important driver in reducing poverty. Some theories, however, claim that, by reducing information and transaction costs, the development of bank-based financial systems could exert a particularly large impact on the poor. This paper looks at a sample of 47 developing economies from 1984 through 2008. The results suggest that when institutions are weak, bank-based financial systems are better at reducing poverty and, as institutions develop, market-based financial systems can turn out to be beneficial for the poor.